Developmental Screening and Follow-up by Nurses. Issue 6 (November 2015) - Lynch, Brian A.; Weaver, Amy L.; Starr, Stephanie R.; Ytterberg, Karen L.; Rostad, Paulette V.; Hall, David J.; Tucker, Sharon J.
Abstract: Objective: The Ages and Stages Questionnaire (ASQ) and Modified Checklist for Autism in Toddlers (M-CHAT) are commonly used screening tools for developmental delay and autism, respectively. This study aimed to evaluate the effectiveness of implementing 18-month developmental and autism screening by mail, with a standardized follow-up process for abnormal screen results. Methods: Within a prospective cohort study design, parents of 892 children received by mail the 18-month ASQ and M-CHAT questionnaires between December 2008 and September 2009. A registered nurse scored the questionnaires and, if needed, administered follow-up screening or set up a referral to Early Intervention or subspecialty pediatrics. Medical record reviews determined clinical outcomes of children who required intervention after initial screening through September 2010. Additionally, demographic factors were evaluated for association with responding to the questionnaires. Results: The ASQ and M-CHAT questionnaires were returned by 529 (59.3%) of the parents. Parents of White children (390/575 [67.8%]) and those with private insurance (457/660 [69.2%]) were significantly more likely to return screening questionnaires than parents of non-White (64/171 [37.4%]; P < .001) and government-insured children (58/169 [34.3%]; P < .001), respectively. Of the 529 children with returned surveys, 109 (20.6%) did not pass at least 1 of the initial screens and 12 (2.3%) were referred after not passing the follow-up screening process. Conclusions: Developmental and autism screening by mail is not a sufficient method to comprehensively screen a general pediatric population. A nurse-completed, standardized follow-up process after an initial failed developmental screen may increase the yield of appropriate Early Intervention or subspecialty referrals. Abstract : Nurses as developmental screening coordinators can improve the amount of appropriate and needed early intervention and subspecialty referrals for infants with developmental needs.